Andrographolide inhibits osteopontin expression and breast tumor growth through down regulation of PI3 Kinase/Akt signaling pathway - Kumar, S.; Patil, H. S.; Sharma, P.; Kumar, D.; Dasari, Sreekanth; Puranik, Vedavati G.; Thulasiram, H. V.; Kundu, G. C. (Current Molecular Medicine, 2012)
Breast cancer is one of the most common cancers among women in India and around the world. Despite recent advancement in the treatment of breast cancer, the results of chemotherapy to date remain unsatisfactory, prompting a need to identify natural agents that could target cancer efficiently with least side effects. Andrographolide (Andro) is one such molecule which has been shown to possess inhibitory effect on cancer cell growth. In this study, Andro, a natural diterpenoid lactone isolated from Andrographis paniculata has been shown to inhibit breast cancer cell proliferation, migration and arrest cell cycle at G2/M phase and induces apoptosis through caspase independent pathway. Our experimental evidences suggest that Andro attenuates endothelial cell motility and tumor-endothelial cell interaction. Moreover, Andro suppresses breast tumor growth in orthotopic NOD/SCID mice model. The anti-tumor activity of Andro in both in vitro and in vivo model was correlated with down regulation of PI3 kinase/Akt activation and inhibition of pro-angiogenic molecules such as OPN and VEGF expressions. Collectively, these results demonstrate that Andro may act as an effective anti-tumor and anti-angiogenic agent for the treatment of breast cancer.
Keywords: Andrographolide; angiogenesis and breast tumor; migration; osteopontin; PI 3 kinase

Enantioselective reduction of ketones and synthesis of 2-methyl-2,3-dihydro-1-benzofuran catalyzed by chiral spiroborate ester - Patil, H. S.; Nikalje, M. D.; Chopade, A. U.; Chopade, M. U. (Russian Journal of Organic Chemistry, 2021)
Asymmetric reduction of homobenzylic ketones was achieved through the use of chiral spiroborate ester catalyst. The catalyst is applicable for both analytical and industrial purposes since it is not sensitive to air and moisture. A rapid synthetic route has been developed for the preparation of (S)-2-methyl-2,3-dihydro-1-benzofuran via enantioselective reduction of homobenzylic ketone in the presence of a chiral spiroborate catalyst as the key step.
Keywords: 2-methyl-2; 3-dihydro-1-benzofuran; asymmetric reduction; spiroborate ester